Catastrophic antiphospholipid syndrome: Lessons from 14 cases successfully treated in a single center. A narrative report. (September 2018) - Ruffatti, Amelia; De Silvestro, Giustina; Marson, Piero; Tonello, Marta; Calligaro, Antonia; Favaro, Maria; Del Ross, Teresa; Hoxha, Ariela; Mattia, Elena; Pengo, Vittorio
Abstract: The study aimed to evaluate the clinical significance of laboratory findings in patients with catastrophic antiphospholipid syndrome (CAPS) and to report the effects of a well-defined treatment protocol in 14 consecutive cases. Thirteen patients (12 presenting one and one presenting two episodes of CAPS) were consecutively treated and monitored between 1986 and 2017. Antiphospholipid antibody (aPL) characteristics of the patients were compared with those of 64 matched controls (45 antiphospholipid syndrome patients and 19 aPL carriers) who did not develop CAPS during the same mean follow-up period (12 years ± 9.9 SD). Triple aPL positivity (IgG/IgM anticardiolipin + IgG/IgM anti-β2Glycoprotein I + lupus anticoagulants) significantly prevailed in the CAPS patients with respect to the controls (p = 0.003). IgG anticardiolipin and IgG anti-β2Glycoprotein I mean antibody titers of the CAPS patients were significantly higher than those of the controls (p = 0.0018 and p = 0.003, respectively). Triple therapy (anticoagulation + plasma exchange + steroids) was administered to all the CAPS cases except for one. Beginning in 2009, intravenous immunoglobulin infusion has also been included in the triple therapy protocol (six patients). All the patients recovered from CAPS; five showed renal failure and one a I-II class New York Heart Association (NYHA) dilated cardiomyopathy. Long-term outcomes of CAPS included a gradual worsening of renal failure in one patient who required hemodialysis 30 years after the acute episode. Renal function improved in the other four patients. The patient affected with dilated cardiomyopathy worsened to a II class NYHA over a five year period. Currently all the patients are alive. A specific antiphospholipid antibody profile could be considered a risk factor associated to CAPS. Early use of a defined treatment protocol based on triple therapy either or not associated with IVIG was associated with recovery in all CAPS patients. Highlights: Triple antiphospholipid positivity could be considered a diagnostic tool of CAPS. High antiphospholipid levels could be considered another diagnostic tool of CAPS. Used early, a well-defined treatment protocol seems to reduce CAPS mortality.